Students Ethics in the Kitab Adab Al-‘Alim Wa Al-Muta’allim By Hasyim Asy’ari in Contemporary Perspective - Rohman, Fatkhur; Dahlan, Zaini (Fitrah: Journal of Islamic Education, 2025)
The rapid pace of societal change demands that educators understand the foundation of true values. Kitab Adab Al-'Alim Wa Al-Muta'allim by KH. Hasyim Asy'ari is one such foundation that remains relevant to this day. This study aims to analyze the various ethical principles for students contained within Kitab Adab Al-'Alim Wa Al-Muta'allim and explore the implications of these concepts in the practice of contemporary Islamic education. As a monumental work, this book presents broad concepts with the potential to be applied across various levels of formal education, from primary school to higher education. This research employs a qualitative method with a library research approach, relying on content analysis of the primary text and supported by secondary literature. The findings reveal that Kitab Adab Al-'Alim Wa Al-Muta'allim emphasizes the importance of ethics in the pursuit of knowledge, the relationship between students and teachers, as well as ethics in learning, such as sincerity, respect for teachers, dedication to learning, and courtesy. Kitab Adab Al-'Alim Wa Al-Muta'allim can serve as a valuable reference for addressing contemporary issues in Islamic education, such as the tendency of education practitioners to become trapped in academic routines while neglecting the moral and character development of students.